Improved assembly and variant detection of a haploid human genome using single‐molecule, high‐fidelity long reads. (11th November 2019) - Vollger, Mitchell R.; Logsdon, Glennis A.; Audano, Peter A.; Sulovari, Arvis; Porubsky, David; Peluso, Paul; Wenger, Aaron M.; Concepcion, Gregory T.; Kronenberg, Zev N.; Munson, Katherine M.; Baker, Carl; Sanders, Ashley D.; et al.
Abstract: The sequence and assembly of human genomes using long‐read sequencing technologies has revolutionized our understanding of structural variation and genome organization. We compared the accuracy, continuity, and gene annotation of genome assemblies generated from either high‐fidelity (HiFi) or continuous long‐read (CLR) datasets from the same complete hydatidiform mole human genome. We find that the HiFi sequence data assemble an additional 10% of duplicated regions and more accurately represent the structure of tandem repeats, as validated with orthogonal analyses. As a result, an additional 5 Mbp of pericentromeric sequences are recovered in the HiFi assembly, resulting in a 2.5‐fold increase in the NG50 within 1 Mbp of the centromere (HiFi 480.6 kbp, CLR 191.5 kbp). Additionally, the HiFi genome assembly was generated in significantly less time with fewer computational resources than the CLR assembly. Although the HiFi assembly has significantly improved continuity and accuracy in many complex regions of the genome, it still falls short of the assembly of centromeric DNA and the largest regions of segmental duplication using existing assemblers. Despite these shortcomings, our results suggest that HiFi may be the most effective standalone technology for de novo assembly of human genomes.